Psychometric validation of the Core Self-Evaluations Scale in people with spinal cord injury. Issue 9 (23rd April 2016) - Smedema, Susan Miller; Morrison, Blaise; Yaghmaian, Rana A.; Deangelis, Jesse; Aldrich, Holly
Abstract: Purpose : Core self-evaluations (CSE) are the perceptions that people have about their overall worth and capability. CSE may be a useful global indicator of adaptation to disability and subjective well-being. The Core Self-Evaluations Scale (CSES) is the most common direct measure of CSE, but its use with persons with disabilities has not been validated. This study aims to evaluate the factorial and concurrent validity of the CSES in persons with spinal cord injury. Method : Two hundred forty-seven individuals with spinal cord injury completed an online survey consisting of the CSES, measures of the four CSE traits, and selected psychosocial variables. Results : Confirmatory factor analysis results provide support for the one-factor measurement structure of the CSES. When correlated with selected psychosocial variables, the CSES was found to perform in a similar fashion to an indirect measure of CSE constructed from measures of the individual CSE traits. Conclusions : The CSES demonstrated acceptable psychometric properties, and its use as a brief, cost-effective measure of CSE in rehabilitation research and practice is supported. Implications for Rehabilitation: Core self-evaluations (CSE) are the perceptions that people have about their overall worth and capability, and the construct has promise as a global indicator of adaptation to disability and subjective well-being in rehabilitation research and practice. The Core Self-Evaluations Scale (CSES) is a brief, valuable and cost-effective instrument that can be easily used in both rehabilitation research and practice and has the potential to reduce burden associated with client/participant assessment. This study provided evidence of the factorial and concurrent validity of the CSES in persons with spinal cord injury, and supports its use in rehabilitation settings.